Control of Defensive Organization in the Battle of Leningrad - Valery Pavlovich Gridnev (Управленческое консультирование)
Article is devoted to governing bodies and their officials performing management of creation of defensive works during fight for Leningrad. During the analysis of their management activity progress, and also management system shortcomings are shown that allows in the conditions of threats and challenges to make use of its experience in the solution of tasks on strengthening of economic and defensive power of Great Russia, activization of military patriotic education of younger generation. In article active participation of Army and inhabitants in defense of the city, their heroism reveals.